2018
DOI: 10.1017/ice.2018.169
|View full text |Cite
|
Sign up to set email alerts
|

Improving fluoroquinolone use in the outpatient setting using a patient safety initiative

Abstract: We analyzed the impact of a fluoroquinolone patient safety initiative on the weekly fluoroquinolone prescription rate in Veterans Affairs community-based outpatient clinics. We observed a significant initial but unsustained reduction. Such an initiative can function as an antimicrobial stewardship intervention; however, strategies to promote sustainability should be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…This approach could result in a more objective quantification of overall antimicrobial usage. 23 This study had several limitations. First, given the retrospective nature of the study, it is difficult to determine whether additional external factors other than the assessed interventions might have affected the study results.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This approach could result in a more objective quantification of overall antimicrobial usage. 23 This study had several limitations. First, given the retrospective nature of the study, it is difficult to determine whether additional external factors other than the assessed interventions might have affected the study results.…”
Section: Discussionmentioning
confidence: 93%
“…In various antimicrobial stewardship interventions for providers and patients, collateral effects on control groups or unintended populations were not uncommon. 23,24 Because most primary care providers and pediatricians care for children in all age groups, collateral effects could explain the broader effect of the educational intervention. The implementation of financial incentives, in contrast, had been strictly limited to those aged 0-2 years; therefore, it is unlikely to influence prescription practice on the other age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, this intervention occurred after the improvement team visited CBOCs, meeting and interviewing providers to learn about processes and barriers at each site, which built rapport and made individualised reviews easier. Comparison feedback emails have been shown to be both ineffective 35 and effective 24 25 36-39 in increasing provider guideline adherence. Although there was some reduction in prescribing with implementation of feedback emails, the reduction was not sustained once the intervention was removed.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, Rodrigues AT et al [38] found that relative prescription of fluoroquinolones showed no changes after intervention, which were attributed to the association of these prescriptions in primary care with disease condition and patient's age, making it more difficult to change prescribing behaviors in such cases. Jindai K et al [39] discovered an initial reduction on fluoroquinolone prescribing rate after implementing fluoroquinolone safety initiative but was not sustained later, calling for sustainable strategies. Future stewardship should not only specifically target fluoroquinolone use but also combine ongoing approaches to enhance the sustainability of intervention.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%